2009
DOI: 10.3354/meps08082
|View full text |Cite
|
Sign up to set email alerts
|

Co-occurrence and aggregation of marine birds and mammals in Monterey Bay, California, USA

Abstract: Patterns of spatial and temporal co-occurrence or avoidance among different species of marine birds and mammals can provide insights into the degree to which these top predators compete for prey. I conducted at-sea surveys in nearshore waters of Monterey Bay, California, USA, and used a randomization technique to assess co-occurrence patterns of marine birds and mammals in 1 km transect segments. As expected, strongest positive associations were among members of 3 different foraging guilds: pursuit-divers, sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 65 publications
0
9
0
Order By: Relevance
“…Inter-specific competition has been suggested to reduce foraging efficiency in some pursuit-diving species (Henkel, 2009). That study was based on surveys at sea over 2 years, and suggested more intense competition (i.e.…”
Section: Avoidance Of Competitionmentioning
confidence: 99%
“…Inter-specific competition has been suggested to reduce foraging efficiency in some pursuit-diving species (Henkel, 2009). That study was based on surveys at sea over 2 years, and suggested more intense competition (i.e.…”
Section: Avoidance Of Competitionmentioning
confidence: 99%
“…Due to space limitations or advantages in predator defense, mixed-species colonies with several simultaneously breeding species as well as adjacent colonies of two different species are widespread among seabirds (e.g., Prince 1980, Frere et al 2008). Yet, inter-specific competition has been found to reduce foraging efficiency in some pursuit-diving species (Henkel 2009). In those seabird communities, inter-specific competition is at least partially avoided by ecological segregation, such as species-specific differences in foraging areas (e.g., Croxall and Prince 1980, Trivelpiece et al 1987, Weimerskirch et al 1993, Frere et al 2008, Wilson 2010, diving depths (e.g., Boyd 2004, Wilson 2010), diet choice (e.g., Baltz et al 1979, Ridoux 1994, Kato et al 1996, Weiss et al 2009), or diurnal foraging patterns (Wilson 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In the oceans, the more productive areas are often in cold-water or upwelling regions where higher nutrient availability sustains productive food webs. Seabird species often breed in large communities and target productive areas within their foraging range, leading to intense competition for resources [1] and reduced foraging efficiency [2]. Seabirds can avoid interspecific competition at least partially by ecological segregation in foraging areas [3,4], diving depths [4,5] or diet choice [6,7].…”
Section: Introductionmentioning
confidence: 99%